Big 5 Personality (Ocean Model), Knowledge, and Motivation as Factors Influencing Entrepreneurial Interest Among Students - Febriana, Artha; Sugiarti, Rini; Erlangga, Erwin (Jurnal Penelitian Ekonomi dan Bisnis, 2025)
Big five personality and entrepreneurial knowledge have an influence in increasing entrepreneurial motivation and entrepreneurial interest among students. Entrepreneurial interest among students is not only influenced by individual personality but also by the breadth of entrepreneurial insight that students have, which ultimately makes students have the drive and interest to become entrepreneurs. The purpose of this study was to examine the influence of big five personality and entrepreneurial knowledge on entrepreneurial motivation and entrepreneurial interest among students. The purposive sampling technique was based on the criteria of individuals who received entrepreneurial knowledge at school or college, and who were born between 2000 and 2005. Based on these criteria, there were 264 people who could be used as research samples. Quantitative analysis in this study used IBM AMOS 26. In this study, big five personality was able to positively influence entrepreneurial motivation and entrepreneurial interest of students. In addition, entrepreneurial knowledge also positively influenced entrepreneurial motivation and entrepreneurial interest of students. The better the big five personality and entrepreneurial knowledge possessed by students, the greater the entrepreneurial motivation and interest of students to become entrepreneurs. The good big five personality and the amount of entrepreneurial knowledge possessed by students will direct their behavior to develop creativity, dare to take risks and be able to turn their ideas into real actions.